A potential carrier for anti-tumor targeted delivery-hyaluronic acid nanoparticles. (15th March 2019) - Cai, Jia; Fu, Jingru; Li, Ruirui; Zhang, Fang; Ling, Guixia; Zhang, Peng
Graphical abstract: Highlights: The mechanism of the uptake and drug release of HA nanoparticles are elaborated. The synthesis of HA nanoparticles is reviewed in detail from several aspects. The latest applications of HA nanoparticles in delivery are summarized clearly. Some modification strategies are discussed for further improving the targeting and drug releasing characteristics. Abstract: In recent years, biomacromolecules have been widely used in anti-tumor delivery systems due to the biocompatibility and biodegradability. However, their applications are limited due to the lack of specific targeting. Hyaluronic acid (HA) is a natural polysaccharide and presents in extracellular matrix and synovial fluid which can specifically recognize receptors over-expressed by tumor cells. In addition, they can self-assemble into nanoparticles. HA nanoparticles provide new hierarchical targeting strategies: passively targeting tumor tissue by enhanced permeability and retention effect, actively targeting tumor cells by cluster determinant 44 (CD44) receptor, and then entering cells through receptor-mediated endocytosis. In this review, the synthesis of HA nanoparticles is described in detail from several aspects and applications are also discussed for improving the delivery of hydrophobic drugs, nucleic acids and photosensitizers into the tumor cells. In addition, the modification of HA for improving the targeting and drug releasing characteristics are also discussed.